Intellectual capital strategy management for knowledge-based organizations - Ordóñez de Pablos, Patricia 1975-; Tennyson, Robert D.; Zhao, Jingyuan 1968- (Premier reference source, 2013)
"This book brings together new perspectives on the knowledge-based view of strategy management as it considers the role of companies, organizations, and nations in the storage and measurement of their knowledge" - Provided by publisher